Assessing meat quality and textural properties of broiler chickens: the impact of voltage and frequency in reversible electrical water-bath stunning - Hayat, Muhammad Nizam; Ismail-Fitry, Mohammad Rashedi; Kaka, Ubedullah; Rukayadi, Yaya; Ab Kadir, Mohd Zainal Abidin; Mohd Radzi, Mohd Amran; Kumar, Pavan; Nurulmahbub, Nurul Ain; Sazili, Awis Qurni (Elsevier, 2024)
The implementation of the head-only electrical stunning procedure in poultry processing has been aimed at enhancing eating, ethical, and religious quality. However, inconsistencies in voltage and frequency standardization, along with variations in previous research outcomes, have led to numerous cases of both under-stunned and over-stunned birds. Thus, this study aimed to comprehensively evaluate the effects of varying voltages and frequencies during electrical water bath stunning on carcass quality, meat attributes, and textural properties in broiler chickens. A cohort of 240 healthy female broilers (Cobb 500, 42-days-old, 2 kg ± 0.1 kg) was meticulously selected from a commercial farm. The birds underwent exposure to different stunning voltages (2.5, 10.5, 30, and 40 V) and frequencies (50 and 300 Hz). Subsequent analyses were conducted on meat samples to assess physicochemical properties, carcass quality, and textural attributes. The findings revealed a higher incidence of petechial hemorrhage (P < 0.05) in birds stunned at 10.5 V compared to other voltage. Notably, no broken bones were recorded in birds subjected to high voltages (30 and 40 V). Low frequency (50 Hz) significantly increased the occurrence of petechial hemorrhage and simultaneously resulted in pectoralis major muscle with decreased redness (a*). Birds subjected to the 10.5 V stunning treatment exhibited a lower cooking loss percentage. Significant interactions between voltage and ageing (V × A) were observed. Birds stunned at 30 V and aged for 7 d displayed highest drip loss compared to a one-day ageing period across different voltage levels. This interaction also impacted pH values, with birds subjected to 10.5 V showing significantly lower (P < 0.05) pH at d 7 of ageing. The meat hardness was influenced by the V × A interaction, wherein birds stunned at 10.5 V exhibited lower hardness after one day of ageing compared to other voltage levels. Red wing tips, lightness (L*), adhesiveness, and resilience were also significantly impacted (P < 0.05) by the interaction between frequency and voltage. A notable 3-way interaction was observed for gumminess and chewiness (F × V × A), where the 2-way interaction between frequency and voltage (F × V) affected both parameters differently at various ageing periods. Additionally, there was a significant interaction (P < 0.05) between frequency and voltage influencing shear strength and yellowness.